(untitled) (Experimental biology, 2015)
Cell surface proteins in mammals are typically elaborated with a complex array of glycans. N-acetyl neuraminic acids (abbreviated as Sialic acids), are usually found at the non-reducing terminal position of these glycans. This terminal glycan sialylation imparts a negative charge at physiological pH values and mediates many biological functions. Here,we utilize two human mammary epithelial cell lines, MCF10A (breast normal cells) and MCF7 (breast cancer cells)as a model system to show differential glycan terminator when treated with sialic acid under nutrient deprivation.Under starved condition, sialic acid treatment of both cells resulted increased activities of α2→3/6 sialyltransferases as demonstrated by lectin solid phase assay. The presence of increased sialyltransferase expression is corroborated by stronger binding with sialic acid-specific lectins such as (Sambucus nigra agglutinin, SNA) and (Maackia amurensis agglutinin I, MAL-I). However, MAL-I binding discriminates malignant cells from normal cells suggesting a preferential increase of Neu5Acα2→3Gal on the SA-treated malignant cell surface.